PENCEGAHAN KERUSAKAN LINGKUNGAN MELALUI INSTRUMEN HUKUM ADMINISTRASI - Erwin Indra Putra (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTAdvances in science and tehknologi rapidly growing in the West since the 17th century has brought a variety of changes in value (value migration) in manusia.Kondisi civilization thus forcing other countries, especially third world countries to pursue world in the development of science and tehknologi Meanwhile the third world people's lives, is still experiencing a transition from an agrarian society to a life pattern pattern patterned industry masyarakaat life